Multifunctional hybrid materials based on transparent poly(methyl methacrylate) reinforced by lanthanoid hydroxo clusters - Andrews, P.; Brown, David; Fraser, B.; Gorham, Nicole; Junk, P.; Massi, Massimiliano; St Pierre, T.; Skelton, B.; Woodward, R. (The Royal Society of Chemistry, 2010)
Three pentanuclear lanthanoid hydroxo clusters of composition [Ln(OH)5(abzm)10], where Ln = Eu, Tb,Ho and abzm = di(4-allyloxy)benzoylmethanide, have been prepared. The structures have beencharacterised by means of IR, Raman, elemental analyses and X-ray diffraction, showing a pyramidalsquare-based cluster core. The clusters (Tb and Ho) exhibit Curie?Weiss Law behaviour, displayingantiferromagnetic ordering at low temperatures. The emission properties of the Eu cluster demonstratethe abzm- ligand is an efficient antenna (lex = 420 nm) only for the sensitisation of Eu luminescence inthe visible range, via energy transfer to the 5D0 state of the trivalent metal. The clusters have beenreacted in the presence of methyl methacrylate and azobisisobutyronitrile to prepare reinforcedpolymers via radical polymerisation. The obtained materials exhibit swelling upon immersion intoorganic solvents up to 110% of their original size, in agreement with the presence of cluster-crosslinked polymeric chains. Also, no loss of transparency was observed in the preparation of the materials. The characteristic red emission of the Eu cluster in also retained in the polymeric material.